Effects of high quality nursing combined with fat emulsion parenteral nutrition support on nutritional status and lipid metabolism of elderly colon cancer patients: Fat emulsion parenteral nutrition support for colon cancer patients - Yilian Chen,; Zhong, Hai; Jing Feng, (Progress in Nutrition, 2021)
High quality nursing combined with fat emulsion parenteral nutrition support can significantly improve the nutritional status and lipid metabolism of elderly patients with colon cancer. The incidence of hunger and thirst in the observation group was significantly lower than that in the control group. After the operation, the time of exhaust, defecation, feeding and hospitalization in the observation group were significantly shorter than those in the control group. Serum levels of pre-albumin and albumin, triglyceride, cholesterol and complication rate in the observation group were significantly lower than those in the control group.